A special schedule of foliar application of nutrients for the tea fields under extensive mechanized harvesting - J Ilango, R. Victor; Kumar, P. Mohan; Parthibaraj, R.; Kumar, B. Suresh; Govindaraj, R.; Mareeswaran, J.; Chaudhuri, T.C. (Journal of Plantation Crops, 2012)
To overcome the problem of acute shortage of work force faced by the south Indian tea industry, UPASI Tea Research Institute recommends mechanized harvesting to cover large areas with high worker productivity. While adopting extensive mechanized harvesting, total leaf area of the maintenance foliage on the plucking surface is reduced. As a result growth of the crop shoots has been adversely affected leading to reduction in productivity. Excessive banji shoot formation and nutrient deficiency symptoms were also noticed. To overcome all these adverse impacts of extensive mechanization, foliar application of primary, secondary and micro-nutrients has been attempted. The practical utility of foliar feeding of all these nutrients when applied as a mixture after every harvest, except during continuous heavy rainy months, showed an increase in yield up to 21% compared to the current recommended practice, in spite of extensive harvesting using shears and machines. The problem of dwarfing of crop shoots due to extensive shear/machine harvesting could be minimized due to increase in internodal length by 0.87 cm and the dry weight of the crop shoots increased by 0.09 g/shoot. Excessive production of banji shoots also came down from 65 to 52%.